Evidence of Validity for a Newly Developed Digital Cognitive Test Battery - Vermeent, Stefan; Dotsch, Ron; Schmand, Ben; Klaming, Laura; Miller, Justin B.; van Elswijk, Gijs (Frontiers in Psychology, 2020)
Clinical practice still relies heavily on traditional paper-and-pencil testing to assess a patient’s cognitive functions. Digital technology has the potential to be an efficient and powerful alternative, but for many of the existing digital tests and test batteries the psychometric properties have not been properly established. We validated a newly developed digital test battery consisting of digitized versions of conventional neuropsychological tests. Two confirmatory factor analysis models were specified: a model based on traditional neuropsychological theory and expert consensus and one based on the Cattell-Horn-Carroll (CHC) taxonomy. For both models, the outcome measures of the digital tests loaded on the cognitive domains in the same way as established in the neuropsychological literature. Interestingly, no clear distinction could be made between the CHC model and traditional neuropsychological model in terms of model fit. Taken together, these findings provide preliminary evidence for the convergent and discriminant validitystructural validity of the digital cognitive test battery.